Community Perception of Water Distributive Justice: The Case of Lebak Siliwangi, Bandung - Septiani, Aulia Irina; Bhebhe, Maria Dolorosa; Amalia, Ghina; Hidayat, Muhammad Afif; Bashir, Imam Abdullah (Department of Urban and Regional Planning, Universitas Diponegoro, 2025)
Access to clean water in urban areas is generally higher than in rural areas. However, clean water services are not always optimal or in accordance with established standards. Fair water distribution is essential to ensure that clean water is provided to the community in line with the principles of quality, quantity, continuity, accessibility, and affordability, both from formal and informal sources, and for different community groups, including marginalized and low-income households. This study aims to examine community perceptions regarding the fairness of clean water service distribution in Lebak Siliwangi Village, Bandung City. A qualitative descriptive approach was employed, using data obtained through observations, interviews, and literature review. The findings reveal that significant gaps remain in water service distribution. Water source from Local Water Supply Utility (PDAM) generally provides better service but does not reach all community groups equally. Meanwhile, informal sources cover wider areas but face persistent challenges related to quality, quantity, and continuity. Community perceptions indicate that tariffs in some areas are still considered disproportionate to service quality, particularly for households with greater water needs. These results suggest that optimizing distribution networks, monitoring water quality, improving infrastructure, and encouraging community participation are key strategies to ensure inclusive and equitable clean water services.